Effect of Soiling on the Performance of Solar PV Modules: A Case Study of Aligarh. Issue 2 (3rd April 2021) - Tariq, Mohd; Ansari, Mohsin Karim; Rahman, Fazlur; Rahman, Md Atiqur; Ashraf, Imtiaz
ABSTRACT: The world's future is with renewable energy resources and solar energy which is a clean and sustainable energy resource. Solar PV module is exposed to external environments where dust deposits are a major derogatory factor. The soil and its effect on the performance of the solar module is usually a matter of high concern for the areas of high density and high frequency of low frequency and low-intensity rainfall. Due to the PV module, the effects of dust are examined in relation to various types of dust concentration and spectral transmission. For examination and analysis, experimental investigation is reported in the paper. The investigation shows that dust effects are accumulated, i.e., the performance of the PV module decreases over time with increasing statements, or until it is cleaned manually or through rain. It is also observed that the inclination of the PV installation plays a major role in the quantity of dust deposited on the angle equipment, where the concentration of dust is reduced as a result of higher tilt angles. Aligarh, with its irregular environmental conditions, suffers from high air pollution and minimum rainfall during dry winter. In this study, the impact of dust on the PV module is examined in relation to the dust density of the dust and the meteorological variables for Aligarh, with the purpose to calculate the drop equation describing efficiency loss. Graphical abstract: